Colombia : territorial rule and the Llanos frontier - Rausch, Jane M., 1940- (University Press of Florida, 1999)
"Fascinating and well-researched account of the efforts by the three Colombian presidents who ruled during the so-called 'Liberal Republic' (1930-46) to develop and incorporate the vast expanses of territory to the east of the Andes known commonly as the Llanos. Concludes that although some progress was made in the more accessible departments of Meta, Arauca, and Casanare, the reforms 'did not change the basic structure of the Llanos frontier or its relationship to the highlands as it had been developing over the previous three centuries' (p. 216). Instead, the advent of the Violencia largely halted efforts and reinforced status of eastern Colombia as a haven for people fleeing from conflict elsewhere. Essential reading for anyone wishing to better understand why the Llanos became the focus of the Colombian drug trade and the main stronghold of the country's largest guerrilla force"--Handbook of Latin American Studies, v. 58.